2020
DOI: 10.3389/fphar.2020.532568
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor Erythroid 2 Related Factor 2 Activator JC-5411 Inhibits Atherosclerosis Through Suppression of Inflammation and Regulation of Lipid Metabolism

Abstract: Phenethyl isothiocyanate is widely present in cruciferous vegetables with multiple biological effects. Here we reported the antiatherogenic effects and the underlying mechanisms of JC-5411 (Phenethyl isothiocyanate formulation) in vitro and in vivo. Luciferase reporter assay showed that JC-5411 increased the activity of nuclear factor erythroid 2-related factor 2 (Nrf2) and antioxidant response element (ARE). JC-5411 treatment significantly increased the protein expression of Nrf2 and its downstream target gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…PEITC has also been reported to significantly increase the activities of Nrf2 and a series of antioxidant enzymes in fibroblasts (21). Mechanistic studies showed that the anti-inflammatory effect of PEITC was driven, at least in part, by inhibiting the NLRP3 inflammasome pathway, as indicated by the downregulation of NLRP3, TXNIP, caspase-1, and IL-1b (34,35). Our results also showed that PEITC can inhibit the expression of NLRP3 and the cleavage of CASP1 (upstream of GSDMD) both in vivo and in vitro (Figures 3, 4A, B, 5G, 6B, C).…”
Section: Discussionmentioning
confidence: 99%
“…PEITC has also been reported to significantly increase the activities of Nrf2 and a series of antioxidant enzymes in fibroblasts (21). Mechanistic studies showed that the anti-inflammatory effect of PEITC was driven, at least in part, by inhibiting the NLRP3 inflammasome pathway, as indicated by the downregulation of NLRP3, TXNIP, caspase-1, and IL-1b (34,35). Our results also showed that PEITC can inhibit the expression of NLRP3 and the cleavage of CASP1 (upstream of GSDMD) both in vivo and in vitro (Figures 3, 4A, B, 5G, 6B, C).…”
Section: Discussionmentioning
confidence: 99%
“…AS is a chronic cardiovascular disease that endangers human health and a multifactorial disease that is influenced by multiple environmental and genetic factors ( Jiang et al, 2020 ). In the early stage of AS, LDL across the vascular endothelium by passive transport or receptor-mediated transcytosis and retained in the arterial wall.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, inhibition of the NLRP3 inflammasome pathway by JC‐5411 could prevent pro‐inflammation in atherosclerosis, thereby producing a therapeutic effect. 44 Specific suppression of NLRP3 could play a protective role against atherosclerosis associated with diabetes. 45 Additionally, inactivation of NLRP3 inflammasome because of Tan IIA treatment could ameliorate atherosclerosis in ApoE −/− mice fed with a high‐fat diet.…”
Section: Discussionmentioning
confidence: 99%